2021
DOI: 10.1016/j.ajhg.2021.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Beyond factor H: The impact of genetic-risk variants for age-related macular degeneration on circulating factor-H-like 1 and factor-H-related protein concentrations

Abstract: Age-related macular degeneration (AMD) is a leading cause of vision loss; there is strong genetic susceptibility at the complement factor H (CFH) locus. This locus encodes a series of complement regulators: factor H (FH), a splice variant factor-H-like 1 (FHL-1), and five factor-H-related proteins (FHR-1 to FHR-5), all involved in the regulation of complement factor C3b turnover. Little is known about how AMDassociated variants at this locus might influence FHL-1 and FHR protein concentrations. We have used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 48 publications
10
44
0
Order By: Relevance
“…In conclusion, our results deepen the understanding of the effects of genetic variation at the extended CFH locus and pinpoint a relevant role of FHR proteins in AMD; these results are also supported by a recent study by Unwin et al 62 We describe the involvement of FHR-2 and FHR-5 in AMD and identify low-frequency CFHR2 and CFHR5 variants with a protective effect on AMD. Our study could set a precedent for the analysis of other GWAS loci and pinpoints FHR proteins as potential targets for developing new AMD treatments where individuals with AMD could be selected on the basis of their genetic profile.…”
Section: Discussionsupporting
confidence: 89%
“…In conclusion, our results deepen the understanding of the effects of genetic variation at the extended CFH locus and pinpoint a relevant role of FHR proteins in AMD; these results are also supported by a recent study by Unwin et al 62 We describe the involvement of FHR-2 and FHR-5 in AMD and identify low-frequency CFHR2 and CFHR5 variants with a protective effect on AMD. Our study could set a precedent for the analysis of other GWAS loci and pinpoints FHR proteins as potential targets for developing new AMD treatments where individuals with AMD could be selected on the basis of their genetic profile.…”
Section: Discussionsupporting
confidence: 89%
“…CFHR1 and CFHR5 are presumed pathogenic since they impede CFH binding to pro-inflammatory lipid peroxidation products 69 , 70 , and induce inflammasome activation 71 , whereas CFHR1 gene deletion is known to be protective for AMD 69 . Indeed, the two-sample MR test analysis revealed that both proteins were causally linked to AMD, consistent with prior MR analyses of factor H-related proteins found causally related to AMD 37 . However, because their cis regions overlap (Supplementary Data 8 ), from which the genetic instruments are selected, it is impossible to say whether one or both are the causal effector.…”
Section: Discussionsupporting
confidence: 80%
“…10 ). Significant increases in all factor H-related proteins, including CFHR1, have also been linked to AMD in recent studies 33 , 37 . Figure 7b–d shows scatter plots with the generalized weighted causal estimate and MR-Egger regression for CFHR1, CFHR5, and FUT5, which were all identified as causal candidates in the MR analysis.…”
Section: Resultsmentioning
confidence: 95%
“…Most reports to date have been inconsistent when measuring systemic FH levels in AMD. For instance, Silva et al [48] and Sharma et al [49] reported reduced levels of FH in AMD cases versus controls, whereas more recent reports with larger patient cohorts failed to detect alternations in systemic FH levels by ELISA due to AMD status [50,51], and no difference in FH levels was found by targeted mass spectrometry [52]. Furthermore, no significant differences have been reported between sera from CFH Y402H genotypes [48].…”
Section: Discussionmentioning
confidence: 99%